2013
DOI: 10.1017/s1047951113000231
|View full text |Cite
|
Sign up to set email alerts
|

Elevated troponin levels in previously healthy children: value of diagnostic modalities and the importance of a drug screen

Abstract: Myocarditis is the most common aetiology of myocardial injury in children. Clinical history remains the basic screening tool; drug screens help identify coronary vasospasms secondary to drug use (22% of our cohort). Patients with anomalous coronaries had exertional symptoms. Initial troponin levels and progression were not diagnostic or prognostic. Catheterisation is of limited value and did not change management. Magnetic resonance imaging with gadolinium enhancement is probably the most useful test when init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…ranging from 0.1 to 0.4 ng/mL (16)(17)(18). Our survey data was consistent with this, as pediatric hospital URLs were much higher than those reported by adult hospital respondents.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…ranging from 0.1 to 0.4 ng/mL (16)(17)(18). Our survey data was consistent with this, as pediatric hospital URLs were much higher than those reported by adult hospital respondents.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…The risk of developing MI in pediatric patients has been reported in numerous case reports. Thankavel et al reviewed 32 cases of pediatric patients and found seven with vasospasms and MI associated with marijuana use [60].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Prior studies have shown that among children and adolescents younger than 20 years of age presenting with chest pain, the most common causes of troponin elevation include myocarditis and vasospasm secondary to drug use. 68 Similarly, several studies have characterized the causes of troponin elevation in older adults with an average age of 60–70 years. 911 Causes of troponin elevation other than acute coronary syndrome in these older cohorts include sepsis, tachycardia, heart failure, pulmonary embolism, stroke, cerebral hemorrhage, and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%